2020
DOI: 10.1111/1756-185x.13992
|View full text |Cite
|
Sign up to set email alerts
|

Disease severity affects myocardial functions in patients with treatment‐naive early rheumatoid arthritis

Abstract: Objectives The cross‐sectional study aimed to assess myocardial functions using global longitudinal strain (GLS) echocardiography and arrhythmia parameters with treatment naive newly diagnosed rheumatoid arthritis (RA) and no clinical evidence of cardiovascular disease (CVD). Methods Seventy seven newly diagnosed treatment‐naive RA patients were enrolled. Disease severity was evaluated according to rheumatoid factor (RF) and anti‐citrullinated protein antibodies (ACPA) positivity, and Disease Activity Score 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…By far the largest body of evidence about this association comes from work in the prototypic chronic inflammatory rheumatic disease, rheumatoid arthritis (RA) and the association between high‐grade inflammation and accelerated atherosclerosis. In their work, Cakmak et al 3 suggest that disease severity in treatment‐naïve patients with early RA associated with lower left ventricular function and higher arrhythmia parameters, supporting the notion that more work is needed with regard to heart failure and to sudden death in patients with RA. In their meta‐analysis of population‐based studies, Kim and Choi 4 demonstrated that patients with spondyloarthropathies (SpA) have a significantly higher risk of myocardial infarction (MI) and stroke compared to the general population; this is not as well‐documented in SpA as it is in RA but this work concurs with the continuously enlarging body of evidence that CVD is a core comorbidity across the whole spectrum of systemic inflammatory RMDs.…”
mentioning
confidence: 91%
“…By far the largest body of evidence about this association comes from work in the prototypic chronic inflammatory rheumatic disease, rheumatoid arthritis (RA) and the association between high‐grade inflammation and accelerated atherosclerosis. In their work, Cakmak et al 3 suggest that disease severity in treatment‐naïve patients with early RA associated with lower left ventricular function and higher arrhythmia parameters, supporting the notion that more work is needed with regard to heart failure and to sudden death in patients with RA. In their meta‐analysis of population‐based studies, Kim and Choi 4 demonstrated that patients with spondyloarthropathies (SpA) have a significantly higher risk of myocardial infarction (MI) and stroke compared to the general population; this is not as well‐documented in SpA as it is in RA but this work concurs with the continuously enlarging body of evidence that CVD is a core comorbidity across the whole spectrum of systemic inflammatory RMDs.…”
mentioning
confidence: 91%
“…Rheumatologic markers can also be used to assess the severity of RA and consequently the risk of HF. This was confirmed by Çakmak et al who measured RF, anti-citrullinated protein antibodies, and DAS28 with creactive protein and concluded that lower left ventricular systolic myocardial function and higher arrhythmia measures were related to the severity of RA [36]. Left ventricular myocardial dysfunction in RA patients was also studied by Cioffi et al whose study was applied to normotensive RA patients [25].…”
Section: Heart Failurementioning
confidence: 74%